Analyzing the financial markets linkages – The subprime crisis case - Kurach, Radosław; Jerzy Stelmach (Publishing House of the Wrocław University of Economics, 2009)
Recent period of an extraordinary financial markets turbulence tends to ask an important question about the sources of this high volatility. “Crisis” seems to be the obvious but far too general answer. Thinking about the consequences of an extreme volatility we should be able to assess the significance of the fundamental and non-fundamental reasons that constitute financial market linkages during the time of crisis. In other words, we need to find out if we really do face contagion. However, before answering this serious question, we think some remarks about the pheno-mena of contagion would be very useful. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 260-268